1996
DOI: 10.1099/00221287-142-4-775
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Sulfobacillus acidophilus sp. nov. and other moderately thermophilic mineral-sulphide-oxidizing bacteria

Abstract: Several isolates of Gram

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(120 citation statements)
references
References 21 publications
3
116
0
1
Order By: Relevance
“…Furthermore, many studies on bioleaching have shown that mixed cultures of acidophiles are frequently more efficient in oxidizing sulfide minerals than corresponding pure cultures (Norris et al 1996;Johnson, 1998). Therefore, it is necessary to understand the microbial community structure in different AMD system, which can improve the metal recovery of bioleaching.…”
mentioning
confidence: 99%
“…Furthermore, many studies on bioleaching have shown that mixed cultures of acidophiles are frequently more efficient in oxidizing sulfide minerals than corresponding pure cultures (Norris et al 1996;Johnson, 1998). Therefore, it is necessary to understand the microbial community structure in different AMD system, which can improve the metal recovery of bioleaching.…”
mentioning
confidence: 99%
“…Many strains are also capable of more than one type of metabolism (e.g. Sulfobacillus acidophilus can oxidize inorganic sources of Fe or S for growth (Norris et al, 1996)). …”
Section: Aj250801)mentioning
confidence: 99%
“…Sulfobacilli are thermo-acidophilic and have been reported to possess ω-cyclohexane fatty acid as a major lipid component, but they differ in nutrition from alicyclobacilli as they are facultatively chemolithotrophic (Dufresne et al, 1996 ;Golovacheva & Karavailo, 1978 ;Norris et al, 1996).…”
Section: Characteristicmentioning
confidence: 99%